2004
DOI: 10.1158/0008-5472.can-04-1449
|View full text |Cite
|
Sign up to set email alerts
|

A Paracrine Loop between Tumor Cells and Macrophages Is Required for Tumor Cell Migration in Mammary Tumors

Abstract: Invasion of tumor cells into the surrounding connective tissue and blood vessels is a key step in the metastatic spread of breast tumors. Although the presence of macrophages in primary tumors is associated with increased metastatic potential, the mechanistic basis for this observation is unknown. Using a chemotaxis-based in vivo invasion assay and multiphoton-based intravital imaging, we show that the interaction between macrophages and tumor cells facilitates the migration of carcinoma cells in the primary t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
1,016
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 1,035 publications
(1,060 citation statements)
references
References 55 publications
35
1,016
1
8
Order By: Relevance
“…Depletion of macrophages effectively blocked metastasis in a mouse model [7]. Thus, disrupt of TAM function will provide a novel approach to develop anti-cancer therapies.Recruitment of macrophages to the proximity of tumors was mediated by CSF-1, a growth factor, secreted by tumor cells [6]. CSF-1 also stimulates the proliferation, differentiation, and survival of macrophages [8].…”
mentioning
confidence: 99%
“…Depletion of macrophages effectively blocked metastasis in a mouse model [7]. Thus, disrupt of TAM function will provide a novel approach to develop anti-cancer therapies.Recruitment of macrophages to the proximity of tumors was mediated by CSF-1, a growth factor, secreted by tumor cells [6]. CSF-1 also stimulates the proliferation, differentiation, and survival of macrophages [8].…”
mentioning
confidence: 99%
“…Previous studies with breast cancer models have shown that macrophages comigrate with cancer cells in response to EGF stimulation in this in vivo invasion assay. 15,23,24 To assess macrophage comigration in HNSCC tumor models, the invasive cells collected from tumors were fixed and stained with a pan-cytokeratin antibody to detect tumor cells and an F4/80 antibody to detect macrophages ( Figure 3A). The relatively weak F4/80 staining is consistent with our previous studies in which the permeabilization required for detection of cytokeratin may reduce the amount of F4/80 detected.…”
Section: Egf Stimulates In Vivo Invasion Of Head and Neck Orthotopicmentioning
confidence: 99%
“…6 cer. 15,23,24 FaDu and UMSCC47 cells were injected into the floor of the mouth of nude mice as orthotopic models of HNSCC. We found that EGF stimulated in vivo invasion of both tumors.…”
Section: In Vivo Invasion Of Hnscc 2861mentioning
confidence: 99%
See 2 more Smart Citations